The Rare Case of an Adult-Onset Xanthogranuloma of the Paranasal Sinuses: A Histological Dilemma. (9th June 2020) - Bastianpillai, J.; Haloob, N.; Panchappa, S. A.; Marais, J.
Abstract : Xanthogranuloma is a rare benign tumour, part of the non-Langerhans cell histiocytosis group, uncommon in adults and even less common in the paranasal sinuses. Despite its benign nature, it mimics neoplasm due to its local effects which can have serious functional consequences depending on the anatomical location. We present the rare case of a young lady who presented insidiously with a maxillary sinus xanthogranuloma and was treated with endoscopic resection. Tissue diagnosis is of paramount importance to guide correct further investigations and management, and we discuss the potential challenge in identifying such a rarely seen pathology.